Healthcare Professionals' Knowledge about Pediatric Chronic Pain: A Systematic Review - Mónica Pico; Carmen Matey-Rodríguez; Ana Domínguez-García; Héctor Menéndez; Simone Lista; Alejandro Santos-Lozano (MDPI AG, 2023)
Pediatric chronic pain is a common public health problem with a high prevalence among children and adolescents. The aim of this study was to review the current knowledge of health professionals on pediatric chronic pain between 15-30% among children and adolescents. However, since this is an underdiagnosed condition, it is inadequately treated by health professionals. To this aim, a systematic review was carried out based on a search of the electronic literature databases (PubMed and Web of Science), resulting in 14 articles that met the inclusion criteria. The analysis of these articles seems to show a certain degree of heterogeneity in the surveyed professionals about the awareness of this concept, especially regarding its etiology, assessment, and management. In addition, the extent of knowledge of the health professionals seems to be insufficient regarding these aspects of pediatric chronic pain. Hence, the knowledge of the health professionals is unrelated to recent research that identifies central hyperexcitability as the primary factor affecting the onset, persistence, and management of pediatric chronic pain.